Réinterpréter les musiques régionales du sud-ouest de la France dans les années 1970-1980 - Bénédicte Bonnemason (In Situ)
In the early 1970s, in southwestern France, as elsewhere in the national territory at the same time as in Europe a little earlier, there was renewed interest in regional musical and choreographic objects that were being reinterpreted, giving rise to a largely amateur practice. Adhering to the themes of modern Occitanism, the reinterpretation movement is distancing itself from folkloric groups whose backward-looking proposal is reduced to the mere activity of spectacular performances. It is motivated by the feeling of creating something new in an opposition to mainstream culture. The paths explored by a collective in which several networks of actors, associative and institutional, intertwine together, create an "art world" populated by collectors, dancers, trainers, musicians, animators, makers of musical instruments, producers of discography... Our aim is to show how the folk music revival of the 70s and 80s was structured in part around the instrumental question: the object and its building. By reviving instruments that have disappeared or fallen into disuse (e.g. the bagpipe called cornemuse landaise), the project aims to specify musical instruments as gascons in order to meet a demand while offering a new musical aesthetic.